2004
DOI: 10.1002/chem.200400416
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Hydrated Electrons (H2O)n with Carbon Dioxide and Molecular Oxygen: Hydration of the CO2 and O2 Ions

Abstract: The gas-phase reactions of hydrated electrons with carbon dioxide and molecular oxygen were studied by Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry. Both CO2 and O2 react efficiently with (H2O)n- because they possess low-lying empty pi* orbitals. The molecular CO2- and O2- anions are concurrently solvated and stabilized by the water ligands to form CO2(-)(H2O)n and O2(-)(H2O)n. Core exchange reactions are also observed, in which CO2(-)(H2O)n is transformed into O2(-)(H2O)n upon collisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 50 publications
9
71
0
Order By: Relevance
“…As shown previously for HCl, O 2 , and CO 2 , [10,22,23,39] this reflects the reactivity of the hydrated electron (H 2 O) n À , which in collisions with acetonitrile reacts to form OH À (H 2 O) m . [25] In principle, uptake of CH 3 CN could also trigger the formation and elimination of a hydrogen atom, but the required selective evaporation of CH 3 CN to rationalize the exclusive formation of MgOH + (H 2 O) m is, in view of the high efficiency of reaction (2), highly improbable.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…As shown previously for HCl, O 2 , and CO 2 , [10,22,23,39] this reflects the reactivity of the hydrated electron (H 2 O) n À , which in collisions with acetonitrile reacts to form OH À (H 2 O) m . [25] In principle, uptake of CH 3 CN could also trigger the formation and elimination of a hydrogen atom, but the required selective evaporation of CH 3 CN to rationalize the exclusive formation of MgOH + (H 2 O) m is, in view of the high efficiency of reaction (2), highly improbable.…”
Section: Resultssupporting
confidence: 73%
“…[7] Quantum chemical calculations corroborate the interpretation of the experiments [7,9] that for n > 14, Mg + (H 2 O) n consist of a doubly charged magnesium ion and a hydrated electron, with the spin density of the system distributed in a site remote from the metal center. [13,21,22] In a combined experimental and theoretical study, we were able to show that Mg + (H 2 O) n also exhibit the chemistry of the hydrated electron [23,24] in reactions with O 2 and CO 2 , albeit with significantly reduced reaction efficiencies. [22] In the uptake of O 2 or CO 2 , the hydrated electron is scavenged by the reactant, and formation of MgOH + does not occur.…”
Section: Introductionmentioning
confidence: 95%
“…e peak corresponding to the uoride ion F − was also absent in the CID spectrum of F − (HF) 3 (Fig. 3c), suggesting an insu cient internal energy of the precursor ion F − (HF) 3 . With regard to this, the internal energy deposited in the precursor ions can be roughly estimated from the E CM .…”
Section: Resultsmentioning
confidence: 99%
“…e estimated energy was consistent with the E CM value of 1.99 eV reported by Wenthold and Squires. 6) On the other hand, the E CM data for F − (HF) 2 and F − (HF) 3 showed that the rst loss of HF from these precursor ions occurred at 1 eV/E CM or lower to form the product ions F − (HF) and F − (HF) 2 , respectively (Figs. 4b and 4c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation